Monarch butterfly - Gibbons, Gail. (New York : Holiday House, 1989)
Describes the life cycle, body parts, and behavior of the monarch butterfly. Includes instructions on how to raise a monarch.
Book Links (A.L.A.)
Elem. School Library Collection
Wilson's Children
4.0
K-3
K-3
Keywords: Monarch butterfly -- xJuvenile literature; Butterflies; Monarch butterfly; Butterflies; Monarch butterflies